Integrasi Konservasi dan Ekonomi: Pembuatan Kolam Silvofishery Kepiting Bakau Bersama Pokmaswas Bina Lestari di Ekowisata Mangrove Lembung - Akhmad Farid; Meria Zakiyah Alfisuma; Mertiara Ratih Terry Laksani; Dinda Shafa Adzania Adelweis; Firman Hidayat (Yayasan Literasi Sains Indonesia, 2025)
This community service activity aims to integrate environmental conservation and coastal community economic empowerment through the implementation of a mangrove crab silvofishery system at Lembung Mangrove Ecotourism, Galis Subdistrict, Pamekasan Regency. The program is carried out in collaboration with Pokmaswas Bina Lestari as the main partner in managing the activities. The implementation methods include socializing the concept of silvofishery and participatory pond construction using local materials such as bamboo, gedek, and waring. Evaluations were conducted on the strength of the pond structure, the effectiveness of water circulation, and the increase in community understanding of conservation. The results of the activity showed increased participation of Pokmaswas Bina Lestari in ecotourism management and the formation of an environmentally friendly and economically productive mangrove crab farming model. This activity not only provided direct economic benefits to the community but also strengthened the ecological function of mangrove forests as a buffer for coastal ecosystems. This silvofishery model has the potential to be replicated in other coastal areas as an effort to develop sustainable conservation-based ecotourism.